Metro liminal painting liminal spaces to resist transience and feelings of surveillance - Aypa, Gillian A.
Metro Liminal explores painting liminal spaces that serve as comfort form the feelings of surveillance from dominant spaces and painting them to confront the transitory nature of places of passsage.